Conocimientos y prácticas del autoexamen mamario en la comunidad de Zamora Huayco, Loja - Ramírez Guerrero, Jessenia Belén (2025)
Introduction: Breast self-examination is defined as breast palpation, which is performed by user in search of any changes in size and/or shape, presence of abnormalities, masses or variations in texture or skin tone and retractions. According to data from the Pan American Health Organization, every year in the Americas more than 462,000 women are diagnosed with breast cancer, and more than 100,000 die from this disease. One of the tools against breast cancer is to develop strategies for early detection of the disease, that is, to identify the pathology at a point in its initial symptomatic clinical phase, and therein lies the importance of encouraging health professionals to identify the symptoms referred by the patient or those clinical signs detected in the EMA. Objectives: to evaluate the level of knowledge of breast self-examination in women of the community of Zamora Huayco, according to age. Methodology: a cross-sectional, descriptive study was carried out. The universe consisting of 1808 women and a sample of 320 women living in the community of Zamora Huayco de Loja, between September-December 2022. The Blossiers 2014 questionnaire was applied, the data were analyzed using Excel and presented in graphs. Results: the ratings with the highest level in the three age groups were: Very Good, Good and Excellent. Conclusions: The population is study showed to have a high level of knowledge of breast self-examination, the group from 41 to 64 years of age is the group that practices breast self-examination the most and it was observed that the majority knows breast self-examination and of this majority a large percentage practices breast self-examination